KAJIAN NILAI BELA NEGARA PADA DESAIN KOSTUM DAN ATRIBUT SUPERHERO PANCA SATRIA - Mahimma Romadhona; Aileena Solicitor El Chidtian; Roziana Febrianita (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2020)
Defending the country is an obligation for every Indonesian, including the younger generation. The younger generation must be inculcated with the ideology of the Pancasila state so that they have strong resilience in facing the threat of terrorism and radicalism. Nationalism and national defense insight possessed by the Indonesian people are considered not high. For this reason, awareness and enlightenment are needed from an early age to foster a love of Indonesia's homeland. This can be done one of them through the application of state defense values in costume designs and superhero attributes named